In service, on common ground: finding commonality between user, architecture and landscape through the ritual of dining - Lehabe, Valerie (School of Architecture, Planning and Geomatics, 2018)
This research is about ﬁnding commonality between seemingly unrelated entities. It seeks to enhance an existing essential service situated on a site that brings together people of all walks of life, i.e. on common ground. By intervening at this level there is an opportunity to adapt the current situation whilst simultaneously encouraging cultural cohesion or perhaps at the very least instigatedialogue. One can assume that the intermediary realm constitutes both the interstitial (the state of being) and the liminal (the state of becoming}. It involves creating spaceswith different pluralities at play. This research situates itself in the intermediary realm by creating an intervention that blurs the boundaries between the building and its context. It also seeks to expand the parameters of Adaptive Reuse to not only intervene at the level of the object but rather adapting beyond the object. by paying close attention to all the relationships at play. The intervention expands on an existing programme situated on a terrainvague site.